Catheter Ablation Improves Mortality and Other Outcomes in Real‐World Patients With Atrial Fibrillation. Issue 11 (2nd June 2020) - Yang, Pil‐Sung; Sung, Jung‐Hoon; Jang, Eunsun; Yu, Hee Tae; Kim, Tae‐Hoon; Uhm, Jae‐Sun; Kim, Jong‐Youn; Pak, Hui‐Nam; Lee, Moon‐Hyoung; Joung, Boyoung
Abstract : Background: It is still controversial whether catheter ablation for atrial fibrillation (AF) improves survival and other outcomes in patients with AF. This study evaluated whether ablation reduces death and other events in nationwide real‐world Asian patients with AF. Methods and Results: From the Korean National Health Insurance Service database, 194 928 adult patients (aged ≥18 years) with newly diagnosed AF were treated with ablation or medical therapy (antiarrhythmic or rate control drugs) between January 1, 2005, and December 1, 2015. Among these patients, this study included 9185 with ablation and 18 770 with medical therapy. The time at risk was counted from the first medical therapy, and ablation was analyzed as a time‐varying covariate. Inverse probability of treatment weighting was used to correct for differences between the groups. After weighting, the 2 cohorts had similar background characteristics. During a median (25th, 75th percentiles) follow‐up of 43 (19, 81) months, ablation of AF was associated with lower incidence and risk of composite outcome, including death, heart failure admission, and stroke/systemic embolism (2.5 and 6.4 per 100 person‐years, respectively; hazard ratio [HR], 0.47; 95% CI, 0.43–0.52; P <0.001), all‐cause death (1.0 and 3.6 per 100 person‐years; HR, 0.41; 95% CI, 0.36–0.47; P <0.001), heart failure admission (0.7 and 1.9 per 100 person‐years; HR, 0.43; 95% CI, 0.37–0.50), and ischemic stroke/systemic embolism (1.1 and 2.8 per 100 person‐years; HR, 0.39; 95% CI, 0.34–0.44) than medical therapy. Conclusions: Ablation may be associated with lower risk of death, heart failure admission, and ischemic stroke/systemic embolism in real‐world Asian patients with AF.